An Analysis of MIF Structural Features that Control Functional Activation of CD74. Issue 9 (17th September 2015) - Pantouris, Georgios; Syed, Mansoor Ali; Fan, Chengpeng; Rajasekaran, Deepa; Cho, Thomas Yoonsang; Rosenberg, Eric M.; Bucala, Richard; Bhandari, Vineet; Lolis, Elias J.
Summary: For more than 15 years, the tautomerase active site of macrophage migration inhibitory factor (MIF) and its catalytic residue Pro1 have been being targeted for the development of therapeutics that block activation of its cell surface receptor, CD74. Neither the biological role of the MIF catalytic site nor the mechanistic details of CD74 activation are well understood. The inherently unstable structure of CD74 remains the biggest obstacle in structural studies with MIF for understanding the basis of CD74 activation. Using a novel approach, we elucidate the mechanistic details that control activation of CD74 by MIF surface residues and identify structural parameters of inhibitors that reduce CD74 biological activation. We also find that N-terminal mutants located deep in the catalytic site affect surface residues immediately outside the catalytic site, which are responsible for reduction of CD74 activation. Graphical Abstract: Highlights: Study of the MIF structural features that control activation of CD74 Mapping of the MIF surface residues involved in interactions with CD74 Correlation between MIF's crystallographic B factors and CD74 activation Detailed analysis of the role of MIF catalytic pocket in activation of CD74 Abstract : Pantouris et al. report the first detailed analysis of the MIF structural features that control activation of CD74. The knowledge gained by this work provides the framework for the development of potent therapeutics that block MIF-CD74 interactions.